2021
DOI: 10.3892/or.2021.8133
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic effect of TERT and its potential therapeutic target in NSCLC (Review)

Abstract: Non-small cell lung cancer (NSCLC), which accounts for ~85% of all lung cancer cases, is commonly diagnosed at an advanced stage and has a high patient mortality rate. Despite the increasing availability of treatment strategies, the prognosis of patients with NSCLC remains poor, with a low 5-year survival rate. This poor prognosis may be associated with the tumor heterogeneity of NSCLC, as well as its acquisition and intrinsic resistance to therapeutic drugs. It has been suggested that combination therapy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…11 TERT point mutation, amplification, rearrangement, and epigenetic modification through the TERT promoter can regulate human TERT (hTERT) expression level, activate telomerase, maintain telomere length, and promote tumor growth. 12 Studies have found that TERT co-mutation with other genes mutations can increase the degree of malignancy of tumors, consistent with an anticipated poor prognosis. 13 Co-occurring genomic alterations have emerged as core molecular and clinical heterogeneity determinants in oncogenedriven lung cancer subtypes.…”
Section: Introductionmentioning
confidence: 87%
“…11 TERT point mutation, amplification, rearrangement, and epigenetic modification through the TERT promoter can regulate human TERT (hTERT) expression level, activate telomerase, maintain telomere length, and promote tumor growth. 12 Studies have found that TERT co-mutation with other genes mutations can increase the degree of malignancy of tumors, consistent with an anticipated poor prognosis. 13 Co-occurring genomic alterations have emerged as core molecular and clinical heterogeneity determinants in oncogenedriven lung cancer subtypes.…”
Section: Introductionmentioning
confidence: 87%
“…We were interested in investigating the GO term groups that differed between the disease‐associated gene signatures, as these may drive the differences in the drug candidate sets. Many of the distinct GO term groups are associated with disease progression or response to therapy [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. For example, the LIHC disease‐associated gene signature from the DESeq2 approach contained up‐regulated GO terms unique for the cell differentiation subgroup compared to the other two signatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these distinct GO term groups are associated with disease progression or response to therapy. [47][48][49][50][51][52][53] Thus, each approach for defining disease-associated gene signature identified different aspects of cancer biology to target via signature reversion.…”
Section: Results: Selection and Evaluation Of Disease-associated Gene...mentioning
confidence: 99%